The Impact of Experience Versus Decision Aids on Patient Preference Toward Virtual Care - Aaron R. Prater; Jack T. McConnell; Nikhil R. Yedulla; Edward L. Peterson; Trevor R. Banka; Charles S. Day (Telemedicine Reports)
Introduction: Virtual care utilization has increased in recent years bringing questions of how to best inform patients regarding their use. Decision aids (DAs) are tools created to assist patients in making informed decisions about their health care. This study seeks to determine whether a DA or previous experience could better educate and influence patient's preference on virtual care. Methods: One hundred fifty participants from an orthopedic clinic of a multi-hospital system were divided into three groups. Group 1 (Virtual Care Cohort) had at least one previous virtual care visit and was surveyed with the Telemedicine Satisfaction Questionnaire (TSQ). Group 2 (In-person with Decision Aid) and Group 3 (In-person without Decision Aid) had no virtual care experience. Group 2 received a validated virtual care DA with a knowledge test. Both groups were also administered the TSQ. Results: After the DA, patients improved their score on 3 of 4 virtual care knowledge questions. Each cohort demonstrated a positive perception of virtual care; however, the specific reasons for their favorable views varied. The DA cohort did not show increased preference toward virtual care compared with the non-DA group and only responded significantly higher regarding encounter comfort. Patients with previous experience in virtual care responded most favorably to the majority of survey questions regarding their virtual care preferences when compared with both virtual care naive cohorts. Discussion and Conclusion: We found that patient experience was the most important factor in influencing patient preference toward virtual care. Although the DA increased their virtual care knowledge it did not increase their preference; therefore, efforts should be placed at encouraging patient to experience virtual care.